Mechanical properties of Sn-0.7Cu/Si 3N 4 lead-free composite solder - Mohd Arif Anuar, Mohd Salleh; Mohd Mustafa Al-Bakri, Abdullah; Muhammad Hafiz, Zan Hazizi; Flora, Somidin; Noor Farhani, Mohd Alui; Zainal Arifin, Ahmad, Prof. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com